Pengaruh Servant Leadership dan Motivasi Kerja Terhadap Organizational Citinzenship Behavior (OCB) dengan Kepuasan Kerja Sebagai Variabel Mediasi pada Kantor Wali Nagari di Kecamatan Tigo Nagari Kabupaten Pasaman - Yummi, Yummi; Putri, Eka Risma (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to determine the effect of Servant Leadership and Work Motivation on Organizational Citizenship Behavior (OCB) with Job Satisfaction as a mediating variable at the Nagari Head Office in the Tigo Nagari Sub-district of Pasaman Regency. The method used is survey analysis with data analysis techniques of outer model testing, inner model testing, and hypothesis testing. The sample in this study is a census that is equal to the population totaling 76 Nagari Officials at the Nagari Head Office in the Tigo Nagari Sub-district of Pasaman Regency. The data analysis technique uses the Partial Least Square (PLS) approach. The results of the research show that servant leadership has a significant positive effect on Organizational Citizenship Behavior (OCB). Work motivation has a significant positive effect on Organizational Citizenship Behavior (OCB). Job satisfaction has a significant positive effect on organizational citizenship behavior (OCB). Servant leadership has a significant positive effect on employee job satisfaction. Work motivation has a significant positive effect on employee job satisfaction. Job satisfaction not mediates the effect of servant leadership on organizational citizenship behavior (OCB). Job satisfaction not mediates the effect of work motivation on Organizational Citizenship Behavior (OCB).